2016
DOI: 10.1016/j.ceramint.2016.08.157
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion and microwave processing of nano-sized ITO powder for the fabrication of transparent conductive oxides

Abstract: Aqueous dispersions of tin-doped indium oxide (ITO) nanopowder were prepared and the effect of the addition of PEG 400, Tween 80 and β-alanine as dispersants was investigated using zeta potential and particle size distribution measurements. Both PEG 400 and β-alanine were found to produce stable dispersions that were used to deposit ITO thin films on glass substrates by dip and spin coating methods. The ITO thin films were heat-treated using both conventional and microwave heat treatment in order to improve th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
(41 reference statements)
0
13
0
Order By: Relevance
“…Films deposited for only 90 seconds were found to be conducting, with the lowest sheet resistance value of 497 Ω/□ and a transparency of 70% at 400 nm, giving a resistivity of 1.99 × 10 −2 Ω.cm. Other materials with similar resistivity include ITO fabricated by different methods 70,71 . Our brief experiment, without optimization, suggested that conducting InN thin films could be fabricated using AACVD.
Figure 5( A ) Carrier concentration determined by Mott Schottky Analysis for various composite nitride thin films; ( B ) Band edges of InN, GaN and composite thin films relative to the RHE reference scale as measured by Mott-Schottky.
…”
Section: Resultsmentioning
confidence: 99%
“…Films deposited for only 90 seconds were found to be conducting, with the lowest sheet resistance value of 497 Ω/□ and a transparency of 70% at 400 nm, giving a resistivity of 1.99 × 10 −2 Ω.cm. Other materials with similar resistivity include ITO fabricated by different methods 70,71 . Our brief experiment, without optimization, suggested that conducting InN thin films could be fabricated using AACVD.
Figure 5( A ) Carrier concentration determined by Mott Schottky Analysis for various composite nitride thin films; ( B ) Band edges of InN, GaN and composite thin films relative to the RHE reference scale as measured by Mott-Schottky.
…”
Section: Resultsmentioning
confidence: 99%
“…Recently, some of the UCL authors reported that ITO thin films could be prepared on glass substrates by dip and spin-coating methods . Aqueous dispersions of “ITO nanopowder” (made via continuous hydrothermal synthesis) were prepared and assessed for stability in a range of surface agents, for example, PEG 400, Tween 80, and β-alanine.…”
Section: Electronics Information and Communication Technologymentioning
confidence: 99%
“…Aqueous dispersions of “ITO nanopowder” (made via continuous hydrothermal synthesis) were prepared and assessed for stability in a range of surface agents, for example, PEG 400, Tween 80, and β-alanine. Both PEG 400 and β-alanine were found to produce stable dispersions that could be used to form good quality films after heat-treating, using both conventional and microwave heat-treatments . All of the films exhibited an average transmittance of >80% over the visible spectrum.…”
Section: Electronics Information and Communication Technologymentioning
confidence: 99%
“…Nevertheless, smaller particle size shown in the HRTEM and FWHM is concerned with Derjaguin, Landau, Verwey and Overbeek (DVLO) theory [12]. In DLVO theory, the potential energy of van der Waals attraction and the potential energy of the electrical double layer interaction [13] are summed to provide a total interaction potential energy between colloidal particles.…”
Section: Resultsmentioning
confidence: 99%